4/9x+4=-5x-3

Simple and best practice solution for 4/9x+4=-5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/9x+4=-5x-3 equation:



4/9x+4=-5x-3
We move all terms to the left:
4/9x+4-(-5x-3)=0
Domain of the equation: 9x!=0
x!=0/9
x!=0
x∈R
We get rid of parentheses
4/9x+5x+3+4=0
We multiply all the terms by the denominator
5x*9x+3*9x+4*9x+4=0
Wy multiply elements
45x^2+27x+36x+4=0
We add all the numbers together, and all the variables
45x^2+63x+4=0
a = 45; b = 63; c = +4;
Δ = b2-4ac
Δ = 632-4·45·4
Δ = 3249
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{3249}=57$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(63)-57}{2*45}=\frac{-120}{90} =-1+1/3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(63)+57}{2*45}=\frac{-6}{90} =-1/15 $

See similar equations:

| 4.05p+14.4=4.50(p+3 | | 7(x+2)-4((2x-1)=18-x | | 7(x-6)=-60 | | 3k+2=2k+4 | | 5/6x-8=-3 | | x=195.5*130 | | 3.1=9.8z | | 2+13=-5{6x-3} | | 9x-91+6x-76=180 | | 5m+14=3m+2 | | 7y+8=8y-2y | | 8=-(4/9)u | | 2+2x+1=-1 | | 6x+17+10x-27=180 | | -4(b+2)-6b=-40-6b | | 1/3m+2/3m=0 | | 130=5(6÷5v) | | 2(p+4)^2+5(p+4)+5=0 | | X+15+x+16=21 | | 0=-3v+2 | | 7y-9-4y=4y-7 | | 8+2x-1=9x | | 8x+15=6x+9 | | 2(4+-1)+3=5t+4+3t | | 2-11+2x=x+2 | | 2(4z-1)=3(7+2) | | 2x+11+2x+3=14 | | 6g+20=2g+28g | | 5m-14=3m+2 | | 78=x+6x+8 | | X-1+x+4=19 | | 5(y+5)-8y=13 |

Equations solver categories